2018
DOI: 10.1002/adma.201705060
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering for Extremely Enhanced Charge Separation and Photocatalytic Hydrogen Evolution on g‐C3N4

Abstract: Reinforcing the carrier separation is the key issue to maximize the photocatalytic hydrogen evolution (PHE) efficiency of graphitic carbon nitride (g-C N ). By a surface engineering of gradual doping of graphited carbon rings within g-C N , suitable energy band structures and built-in electric fields are established. Photoinduced electrons and holes are impelled into diverse directions, leading to a 21-fold improvement in the PHE rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
174
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(189 citation statements)
references
References 33 publications
9
174
0
Order By: Relevance
“…[28] The two characteristic peaks of Mn-C 3 N 4 are not shifted, indicating both the interlayer stacking and the triazine units of C 3 N 4 are not changed by intercalating Mn. [28,29] This is in line with our coordination model with Mn deposited at the central of sixfold cavity in C 3 N 4 , as detailed below. No peak of Mn oxide is detected.…”
Section: Synthesis and Structure Of Mn-c 3 N 4 With Mn-n-c Motifsmentioning
confidence: 98%
See 1 more Smart Citation
“…[28] The two characteristic peaks of Mn-C 3 N 4 are not shifted, indicating both the interlayer stacking and the triazine units of C 3 N 4 are not changed by intercalating Mn. [28,29] This is in line with our coordination model with Mn deposited at the central of sixfold cavity in C 3 N 4 , as detailed below. No peak of Mn oxide is detected.…”
Section: Synthesis and Structure Of Mn-c 3 N 4 With Mn-n-c Motifsmentioning
confidence: 98%
“…All the XPS curves are calibrated by C 1s peak (binding energy at 284.8 eV, Figure S5, Supporting Information). [28,30] Importantly, when Mn is coordinated with C 3 N 4 , the N 1s peak of sp 2 -bonded N in aromatic ring (CNC) shifts to higher binding energies compared with bare C 3 N 4 , indicating the electron transfer from N to Mn domains ( Figure 2a; Figure S6, Supporting Information). And the N 1s peak mainly contains three peaks at 398.8 eV for pyridinic N (CNC), 400.1 eV for pyrrolic N (N-C 3 ) and 401.3 eV related to graphitic N, respectively.…”
Section: Synthesis and Structure Of Mn-c 3 N 4 With Mn-n-c Motifsmentioning
confidence: 99%
“…Bai et al proposed the concept of surface polarization in the Pt–Pd–rGo electrocatalytic system, where the improved hydrogen evolution reaction performance was due to the surface charge polarization caused by Pt and Pd . The surface polarization with graphitic carbon rings on polymeric carbon nitride (g‐C 3 N 4 ) was demonstrated to transport the photoinduced e − and h + in diverse directions, leading to a 21‐times improvement of H 2 evolution rate . Recently, our group reported that the surface hydroxylation, halogenation and oxygen vacancies (OVs) can serve as efficient polarization strategies for advancing surface charge separation, markedly enhancing the photocatalytic activity for H 2 evolution of g‐C 3 N 4 and CO 2 reduction of Bi 2 O 2 (OH)(NO 3 ) and Sr 2 Bi 2 Nb 2 TiO 12 …”
mentioning
confidence: 99%
“…Besides, electrochemical impedance spectra (EIS) tests (Figure c) reveal that 4S‐SSHoMSs‐12 h manifests the smallest semicircle in Nyquist plots, suggesting the lowest charge transfer resistance which facilitates transport and separation of photoexcited electron–hole pairs . Also, 4S‐SSHoMSs‐12 h behaves the highest photocurrent in transient photocurrent spectra (Figure d), suggesting the enhanced generation and transfer of photogeneration electron hole pairs in the photocatalyst . All these results illustrated that 4S‐SSHoMSs‐12 h should be the optimal photocatalyst in generation, separation and transfer of photoinduced charges.…”
Section: Figurementioning
confidence: 87%